High-temperature-resistant low-loss soft magnetic composite material for integrally-formed inductor and preparation method thereof

Through inorganic-organic composite insulation coating technology, a double-layer insulation coating layer is formed, which solves the problems of poor temperature resistance and high loss under high frequency and high temperature conditions, and achieves efficient high temperature resistance and low loss effects.

CN119811820APending Publication Date: 2025-04-11ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411924062.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing soft magnetic powder for integrated molded inductors has problems of poor temperature resistance and high loss under high frequency and high temperature conditions, and cannot meet the working conditions requirements of high-performance electronic communication equipment.

Method used

The inorganic-organic composite insulating coating method is adopted to form a double-layer insulating coating layer by mixing nano-silica powder with resin solution, thereby improving the temperature resistance and loss resistance of soft magnetic powder.

Benefits of technology

It significantly improves the high temperature resistance and low loss characteristics of soft magnetic composite materials, and is suitable for electronic communication equipment under high frequency and high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208790630000021
    Figure BDA0005208790630000021
  • Figure BDA0005208790630000061
    Figure BDA0005208790630000061
  • Figure FDA0005208790620000011
    Figure FDA0005208790620000011
Patent Text Reader

Abstract

The invention relates to the field of inductance materials, and particularly discloses a high-temperature-resistant low-loss soft magnetic composite material for an integrally-formed inductor and a preparation method of the high-temperature-resistant low-loss soft magnetic composite material for the integrally-formed inductor. The preparation method comprises the following steps: uniformly stirring an inorganic-organic composite insulating binder consisting of silicon dioxide, tetraethyl orthosilicate and the like with soft magnetic metal powder, granulating, baking, sieving, and adding a lubricant. The integrally formed power inductor further prepared from the soft magnetic composite material prepared by the method has excellent performance stability under a high-temperature processing or working condition through the dual effects of the high-temperature-resistant composite resin and the nano silicon dioxide, has the characteristics of good magnetic conductivity, low loss and the like, and is low in cost, simple in process and suitable for industrial production. The method is convenient to operate and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of soft magnetic materials, and in particular relates to a high-temperature resistant and low-loss soft magnetic composite material for an integrally formed inductor and a preparation method thereof. Background Art

[0002] With the continuous expansion of the terminal market scale of new generation new energy, communication technology, aerospace, etc., the market demand for inductor components has been rising year by year. At the same time, in order to adapt to the rapid development of 5G communication, power electronics, Internet of Things and automotive electronics, inductor components are driven by terminal applications to develop in the direction of miniaturization, high magnetic permeability, high frequency, low power consumption and integration. Compared with traditional winding inductors, one-piece molded inductors are small in size, closed in magnetic circuit, and have the advantages of strong resistance to electromagnetic interference.

[0003] The one-piece molded inductor mainly uses carbonyl iron powder, iron-silicon-chromium alloy powder and amorphous nanocrystalline alloy powder as raw materials, and then obtains the finished powder after coating, adding adhesive, granulation and other steps, and mixes with coils, terminal electrodes and buries them in compression. High-frequency and miniaturized devices lead to a sudden increase in the local power density of the heating element, which inevitably increases the operating temperature of the device. In addition, in some special terminal applications, such as long-term high-temperature working environment, continuous high-frequency work, and the increasingly widespread application of reflow soldering process, these devices have put forward higher and higher requirements for the temperature resistance of these devices. Epoxy resin, as a thermosetting resin, has good insulation and mechanical properties and low cost. It is widely used in coatings, adhesives, automobiles, aerospace and other fields. It is also one of the most widely used adhesives in the field of inductance. However, due to its poor temperature resistance and high brittleness, the commonly used epoxy resin cannot meet the working conditions of high-performance electronic communication equipment, and increases production costs. In addition, as the operating frequency of the equipment becomes higher and higher, the loss of traditional soft magnetic materials will increase rapidly. At present, the main method used to reduce the total loss is powder insulation coating. According to the type of coating material, it can be divided into organic coating and inorganic coating, but each has its own advantages and disadvantages, such as the poor temperature resistance of organic coating, the unevenness of inorganic coating and the complexity of the process.

[0004] In order to solve the above problems and meet the requirements of high frequency, miniaturization, high temperature resistance and low power consumption of one-piece molded inductors, it is necessary to develop a soft magnetic composite material with high temperature resistance and low loss. Summary of the invention

[0005] In order to overcome the shortcomings of existing soft magnetic powder materials for one-piece molded inductors, the present invention provides a high-temperature resistant and low-loss soft magnetic composite material for one-piece molded inductors and a preparation method thereof, which adopts an inorganic-organic composite insulation coating method to improve the temperature resistance of the soft magnetic powder and reduce the eddy current loss under high frequency, and has very excellent high-temperature performance stability.

[0006] To achieve the above object, the technical solution adopted by the present invention is: A high temperature resistant and low loss soft magnetic composite material for an integrally molded inductor is mainly made by mixing soft magnetic metal powder and an inorganic-organic composite insulating binder. The specific preparation method is as follows: (i) Preparation of inorganic-organic composite insulating adhesive: nano-silica powder is mixed with bisphenol A epoxy resin, phenolic epoxy resin, cyanate resin, thermoplastic resin, curing agent and a first solvent to prepare a nano-silica-resin solution; tetraethyl orthosilicate is dissolved in a second solvent to obtain a tetraethyl orthosilicate solution; the tetraethyl orthosilicate solution is then mixed with the nano-silica-resin solution; a pH adjuster is added; and the mixture is stirred evenly to obtain an inorganic-organic composite insulating adhesive. (ii) Preparation of soft magnetic composite powder: mixing soft magnetic metal powder with the inorganic-organic composite insulating binder, uniformly stirring, granulating, drying, sieving, adding lubricant, and obtaining a high temperature resistant and low loss soft magnetic composite material for one-piece molded inductor. The soft magnetic metal powder is one or more of iron silicon chromium alloy powder, iron nickel alloy powder, iron silicon aluminum alloy powder, carbonyl iron powder, and water vapor combined atomization FeSiBCuNb amorphous nanocrystalline powder.

[0007] The components of the nano-silicon dioxide-resin solution in step 1 and the mass percentage of each component in the soft magnetic metal powder are as follows:

[0008] Wherein, the components included in the tetraethyl orthosilicate solution in step 1 and the mass percentage of each component in the soft magnetic metal powder are as follows: Tetraethyl orthosilicate 1%-3% Second solvent 10%-20%

[0009] Among them, the particle size of the nano-silica powder in the nano-silica-resin solution in step one is 1-100 nanometers, the novolac epoxy resin is one or a mixture of bisphenol A novolac epoxy resin, phenol novolac epoxy resin and o-cresol novolac epoxy resin, the cyanate resin is bisphenol A cyanate resin, the thermoplastic resin is one or a mixture of polycarbonate, polyamide, and polyacrylate, the curing agent is one or a mixture of aliphatic amines, alicyclic amines, aromatic amines, polyamides and polyether amines, and the first solvent is acetone or xylene.

[0010] Wherein, the second solvent in the tetraethyl orthosilicate solution in step 1 is ethanol or ether, and the pH regulator is one of ammonia water or ethylenediamine.

[0011] Furthermore, in step one, the nano-silica powder is preferably lipophilic modified nano-silica, the phenolic epoxy resin is preferably bisphenol A phenolic epoxy resin, the thermoplastic resin is preferably polyacrylate, the curing agent is preferably a mixture of one or more of aliphatic amines, alicyclic amines and aromatic amines, and the first solvent is preferably acetone.

[0012] Furthermore, in step 1, the second solvent of the tetraethyl orthosilicate solution is preferably ethanol, and the pH regulator is preferably ammonia water and the added amount is 0.4%-1% of the mass of the soft magnetic metal powder.

[0013] Furthermore, the stirring time in step 1 is 20-40 minutes.

[0014] Among them, in step 2, the inorganic-organic composite insulating binder and the soft magnetic metal powder are mixed, uniformly stirred for 30-60 minutes, and then granulated, and baked in a vacuum oven at 40-60°C for 60-120 minutes, and then vacuum cooled to room temperature and sieved under a 100-mesh sieve to a 300-mesh sieve, and a lubricant accounting for 0.1-0.3% of the mass of the composite powder is added to the obtained composite powder for mixing, wherein the sieved composite powder preferably takes the powder of the middle particle size portion.

[0015] Preferably, the lubricant is a mixture of one or more of zinc stearate, magnesium stearate and polyamide wax.

[0016] This application has the following beneficial effects: 1. In the present invention, bisphenol A epoxy resin commonly used in the industry is used, and novolac epoxy resin is added to initially enhance its temperature resistance, and while reducing the amount of curing agent, the bonding with the metal powder matrix can also be improved. At the same time, a cyanate resin with similar processing properties to epoxy resin is introduced, and a rigid triazine ring structure is introduced into the epoxy resin molecular chain to form a high cross-linking density copolymer system, which greatly improves the temperature resistance while maintaining its excellent electrical insulation. In addition, by further adding a small amount of thermoplastic resins such as polyacrylate, an propylene unsaturated double bond is introduced at both ends of the epoxy resin molecular chain, the plastic toughness and product appearance qualification rate are improved, and cracking and other problems are reduced. 2. At present, due to the fact that metal powders prepared by gas atomization, water atomization and other methods often do not have complete sphericity, especially nanocrystalline and iron-silicon-chromium alloy powders, the poor sphericity leads to poor coating effect of traditional coating process, and the problem of coating layer breaking is also prone to occur in the subsequent compression molding process. On the basis of the original heat-resistant organic resin solution, nano-silicon dioxide powder and tetraethyl orthosilicate are added as inorganic-organic composite insulating binders prepared as main raw materials to enhance the dispersibility of silicon dioxide insulating particles in the solution, hinder the conduction between metal powders and contact with oxygen, and perform inorganic-organic double-layer insulation coating on the powder material. At the same time, unlike the general inorganic insulating layer, the nano-scale silicon dioxide particles used in the present invention do not form a complete inorganic coating layer, are not easy to break during the pressing process, and are more easily coated on the surface of the metal powder in the resin solution system, and are further isolated from oxygen under high temperature working conditions with heat-resistant resins, reduce powder oxidation, and further improve the heat resistance of the powder. 3. In the present invention, the selected resins can be dissolved in organic solvents such as acetone and mixed with inorganic coating solutions for inorganic-organic mixed coating, which reduces the process flow and has the advantages of simple process, convenient operation, low cost, etc., and is suitable for large-scale industrial production. DETAILED DESCRIPTION

[0017] The high temperature resistant and low loss soft magnetic composite material for the one-piece molded inductor and the preparation method thereof are further described below through examples.

[0018] In the present invention, unless otherwise specified, all raw materials can be purchased from the market or are commonly used materials in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0019] Example 1

[0020] To prepare an inorganic-organic composite insulating adhesive, 6 g of bisphenol A epoxy resin, 2 g of phenolic epoxy resin, 12 g of cyanate resin and 0.8 g of polyacrylate resin were weighed and dissolved in 200 g of acetone, and then 1 g of ethylenediamine curing agent and 15 g of nano-silica powder were added and stirred evenly to obtain a uniformly mixed nano-silica-resin solution. At the same time, 10 g of tetraethyl orthosilicate was weighed and dissolved in 100 g of anhydrous ethanol. After stirring evenly, the two solutions were mixed together, and 8 g of ammonia water was slowly added dropwise to the mixed solution while stirring evenly for 30 minutes to obtain an inorganic-organic composite insulating adhesive.

[0021] An inorganic-organic composite insulating binder is added to 1000g of carbonyl iron powder with D50=10μm to form a mixed slurry, which is evenly stirred for 40 minutes and then granulated. The mixture is baked in a vacuum oven at 50°C for 120 minutes, and then sieved through a 100-mesh to 300-mesh sieve. A composite powder with an intermediate particle size is taken, and a zinc stearate lubricant is added according to 0.3% of the mass of the sieved composite powder to obtain a high-temperature resistant, low-loss soft magnetic composite material for an integrated inductor.

[0022] Example 2

[0023] An inorganic-organic composite insulating adhesive was prepared by weighing 10 g of bisphenol A epoxy resin, 3 g of phenolic epoxy resin, 15 g of cyanate resin and 1.3 g of polyacrylate resin, dissolving them in 200 g of acetone, adding 0.8 g of hexamethylenediamine curing agent and 15 g of nano-silica powder, stirring evenly to obtain a uniformly mixed nano-silica-resin solution, and at the same time weighing 10 g of tetraethyl orthosilicate and dissolving it in 100 g of anhydrous ethanol, stirring evenly, mixing the two solutions together, slowly dropping 8 g of ammonia water into the mixed solution while stirring evenly for 30 minutes to obtain an inorganic-organic composite insulating adhesive.

[0024] An inorganic-organic composite insulating binder is added to 1000g of FeSiBCuNb nanocrystalline powder with D50=10μm to form a mixed slurry, which is evenly stirred for 40 minutes and then granulated. The slurry is baked in a vacuum oven at 50°C for 120 minutes, and then sieved through a 100-mesh to 300-mesh sieve. A composite powder with an intermediate particle size is taken, and a zinc stearate lubricant is added according to 0.3% of the mass of the sieved composite powder to obtain a high-temperature resistant, low-loss soft magnetic composite material for an integrated inductor.

[0025] Comparative Example 1

[0026] The difference between this comparative example and Example 1 is that the steps of preparing the inorganic-organic composite insulating adhesive are as follows: 20.8 g of bisphenol A epoxy resin is weighed and dissolved in 200 g of acetone, and then 1 g of ethylenediamine curing agent and 15 g of nano-silica powder are added, and stirred evenly to obtain a uniformly mixed nano-silica-resin solution, and at the same time, 10 g of tetraethyl orthosilicate is weighed and dissolved in 100 g of anhydrous ethanol. After stirring evenly, the two solutions are mixed together, and 8 g of ammonia water is slowly added dropwise to the mixed solution while stirring evenly for 30 minutes to obtain an inorganic-organic composite insulating adhesive.

[0027] Comparative Example 2

[0028] The difference between this comparative example and Example 1 is that the inorganic-organic composite insulating adhesive used does not contain phenolic epoxy resin.

[0029] Comparative Example 3

[0030] The difference between this comparative example and Example 1 is that the inorganic-organic composite insulating adhesive used does not contain any polyacrylate resin.

[0031] Comparative Example 4

[0032] The difference between this comparative example and Example 1 is that the inorganic-organic composite insulating adhesive used does not contain nano-silicon dioxide powder.

[0033] The composite powders obtained from Example 1, Example 2 and Comparative Examples 1, 2, 3 and 4 were pressed at 800 MPa into magnetic rings with an outer diameter of 12.76 mm, an inner diameter of 7.56 mm and a height of 2.8±0.2 mm. After heat treatment, the magnetic rings were made into coils, and the inductance of the magnetic rings was tested to calculate the magnetic permeability. The power loss of the magnetic rings was tested using an AC BH meter, and the rings were baked in a muffle furnace at 250°C in an air atmosphere for 60 minutes to test the change in magnetic permeability performance.

[0034]

[0035] From the test results of Example 1 and Example 2, it can be seen that the metal soft magnetic composite material samples prepared by this method show excellent temperature resistance after being baked in an air atmosphere at 250°C for 60 minutes, the change value of the effective magnetic permeability is within 3%, and at the same time has low loss characteristics.

[0036] By comparing the test results of Example 1 with those of Comparative Example 2, it can be seen that the addition of phenolic epoxy resin can further enhance the temperature resistance of the sample to a certain extent, while substantially not affecting the properties such as magnetic permeability and loss.

[0037] By comparing the test results of Example 1 and Comparative Example 3, it can be seen that adding polyacrylate resin can increase the plasticity and toughness of the resin system and avoid the problem of sample cracking after annealing.

[0038] By comparing the test results of Example 1 with those of Comparative Example 4, it can be seen that selecting nano-silicon dioxide powder with good dispersibility can make the insulating coating more uniform and dense, while reducing losses, isolating the air and reducing powder oxidation, thereby assisting in improving temperature resistance.

[0039] The above-described embodiments are only some of the preferred solutions of the present invention, but they are not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing an inorganic-organic composite insulating binder for soft magnetic materials, characterized in that: The nano-silicon dioxide-resin solution is mixed with tetraethyl orthosilicate solution, and a pH regulator is added and then uniformly stirred to prepare the mixture. The pH regulator is one of ammonia water or ethylenediamine or a mixture of the two.

2. The method for preparing an inorganic-organic composite insulating binder for soft magnetic materials according to claim 1, characterized in that: The preparation method of the nano-silica-resin solution is as follows: in a heat-resistant resin system in which epoxy resin, cyanate resin and a first solvent are mixed, phenolic epoxy resin is further added to enhance the heat resistance and the bonding strength with the metal interface, thermoplastic resin is added to improve the plasticity and toughness of the system, and nano-silica powder and a curing agent are added to obtain the nano-silica-resin solution.

3. The method for preparing an inorganic-organic composite insulating binder for soft magnetic materials according to claim 2, characterized in that: The epoxy resin is one or a mixture of bisphenol A type and bisphenol F type epoxy resins, the phenolic epoxy resin is one or a mixture of bisphenol A type phenolic epoxy resin, phenol type phenolic epoxy resin and o-cresol type phenolic epoxy resin, the thermoplastic resin is one or a mixture of polycarbonate, polyamide and polyacrylate, the particle size of the nano silicon dioxide powder is 1-100 nanometers, the curing agent is one or a mixture of aliphatic amines, alicyclic amines, aromatic amines, polyamides and polyether amines, and the first solvent is acetone or xylene.

4. The method for preparing an inorganic-organic composite insulating binder for soft magnetic materials according to claim 2, characterized in that: The binder is used to mix with the soft magnetic metal powder. Based on the mass of the applied soft magnetic metal powder, the mass percentage of each component in the nano-silicon dioxide-resin solution to the soft magnetic metal powder is as follows: In addition, the curing agent in the nano-silicon dioxide-resin solution accounts for 1%-5% of the total mass of the epoxy resin, the phenolic epoxy resin, and the cyanate resin-based thermoplastic resin.

5. The method for preparing the inorganic-organic composite insulating binder for soft magnetic materials according to claim 1, characterized in that: The tetraethyl orthosilicate solution is prepared by adding tetraethyl orthosilicate into a second solvent and stirring; the binder is used to mix with the soft magnetic metal powder, and the mass percentage of each component in the tetraethyl orthosilicate solution to the soft magnetic metal powder is as follows, based on the mass of the applied soft magnetic metal powder: Tetraethyl orthosilicate 1%-3% Second solvent 10%-20% The second solvent is ethanol or ether.

6. The method for preparing an inorganic-organic composite insulating binder for soft magnetic materials according to claim 1, characterized in that: The pH regulator is one of ammonia water and ethylenediamine, and the mass percentage of the pH regulator in the soft magnetic metal powder is 0.4%-1%.

7. High temperature resistant and low loss soft magnetic composite material for integrally molded inductor, characterized in that: The inorganic-organic composite insulating binder prepared by the method according to any one of claims 1 to 6 is mixed with soft magnetic metal powder, uniformly stirred, granulated, dried, sieved, and lubricated to obtain a high-temperature resistant and low-loss soft magnetic composite material for an integrally formed inductor.

8. The high temperature resistant and low loss soft magnetic composite material for the integrally molded inductor according to claim 7, characterized in that: The soft magnetic metal powder is a mixture of one or more of iron-silicon-chromium alloy powder, iron-nickel alloy powder, iron-silicon-aluminum alloy powder, carbonyl iron powder and water vapor-atomized FeSiBCuNb amorphous nanocrystalline powder. The uniform stirring time is 30-60 minutes. After granulation, the powder is vacuum dried at 40-60° C. for 60-120 minutes, and then sieved through a 100-mesh 300-mesh sieve. A lubricant accounting for 0.1%-0.3% by weight is added to the obtained composite powder to obtain a high-temperature resistant and low-loss soft magnetic composite material for an integrated inductor.

9. The high temperature resistant and low loss soft magnetic composite material for the integrally molded inductor according to claim 8, characterized in that: The lubricant used is a mixture of one or more of zinc stearate, magnesium stearate and polyamide wax.